Short-Term Response of Deep-Water Benthic Megafauna to Installation of a Pipeline Over a Depth Gradient on the Angolan Slope - Virginia Biede; Virginia Biede; Andrew R. Gates; Simone Pfeifer; Simone Pfeifer; Jane E. Collins; Carmen Santos; Carmen Santos; Daniel O. B. Jones (Frontiers in Marine Science, 2022)
Large structures are introduced into deep-water marine environments by several industrial activities, including hydrocarbon exploitation. Anthropogenic structures can alter ecosystem structure and functioning in many marine ecosystems but the responses on continental margins are poorly known. Here, we investigate the short-term response of benthic megafauna to the installation of a 56 km-long 30 cm diameter pipeline on the Angolan Margin (Block 31) from 700 to 1800 m water depth using remotely operated vehicle imagery. Clear depth-related patterns exist in the density, diversity and community structure of megafauna observed in 2013 prior to pipeline installation. These patterns are altered in a subsequent survey in 2014, three-months after pipeline installation. Significant increases in density, particularly in mid-slope regions are observed. Diversity is generally, but not consistently, enhanced, particularly in the shallower areas in 2014. Clear changes are noted in community structure between years. These changes are primarily caused by increases in the abundance of echinoderms, particularly the echinoid Phormosoma sp. indet. There was no evidence of colonisation of the pipeline in three months by visible fauna. The few large anemones observed attached to the pipe may be able to move as adults. The pipeline appeared to trap organic material and anthropogenic litter, and may enhance available food resources locally as well as providing hard substratum. These results indicate complex and ecosystem-dependent responses to structure installation and caution against simplistic approaches to environmental management.